All Politics Are Local: Nineteenth-Century Mexico Revisited - Mark Wasserman (Latin American Research Review, 2017)
This essay reviews the following works: Popular Politics and Rebellion in Mexico: Manuel Lozada and La Reforma, 1855–1876. By Zachary Brittsan. Nashville: Vanderbilt University Press, 2015. Pp. ix + 220. $55.00 cloth. ISBN: 9780826520449. El jefe político: Un dominio negociado en el mundo rural del Estado de México, 1856–1911. By Romana Falcón. Mexico City: El Colegio de México; El Colegio de Michoacán; CIESAS, 2015. Pp. 9 + 744. $39.99 paper. ISBN: 9786074627381. Independent Mexico: The Pronunciamiento in the Age of Santa Anna, 1821–1858. By Will Fowler. Lincoln: University of Nebraska Press, 2016. Pp. viii + 362. $40.00 paper. ISBN: 9780803225398. Mexico’s Supreme Court: Between Liberal Individual and Revolutionary Social Rights, 1867–1934. By Timothy M. James. Albuquerque: University of Mexico Press, 2013. Pp. ix + 149. $45.00 cloth. ISBN: 9780826353788. Conflict and Carnage in Yucatán: Liberals, the Second Empire, and Maya Revolutionaries, 1855–1876. By Douglas W. Richmond. Alabama: University of Alabama Press, 2015. Pp. ix + 177. $49.95 cloth. ISBN: 9780817318703. Las élites empresariales y la independencia económica de México: Estevan de Antun~ano o las vicisitudes del fundador de la industria textil moderna, 1792–1847. By Evelyne Sanchez. Mexico: Plaza y Valdés Editores, 2013. Pp. ix + 363. $29.95 paper. ISBN: 9786074026177.